Thermal drilling processing on sheet metals: A review - R. Kumar; N. Rajesh Jesudoss Hynes (International Journal of Lightweight Materials and Manufacture, 2019)
Thermal drilling is a sheet metal hole making technique and which is the most cost-effective and extremely high productivity technique in sheet metal fastenings. Especially, the fastening or joining of sheet metals is generally used in all manufacturing and industrial applications. But, by reason of thin sheet metal thickness, these fastenings are seen as a tremendously big problem in production. Different traditional methods are available such as welding of a nut to sheet metal, insert rivet & swelling nuts in the drilled hole, which is generally employed for the applications of screw fastening in order to produce a safe and secure screw fastening situation. Those methods revealed some undesirable effects like lifting & twisting of rivets and nuts, thermal distortion at the welding of nut. These difficulties are entirely eliminated in the thermal drilling process. In this review, the basic working principle of the thermal drilling process, merits, the described experimental setup, used thermal drill tools and different applications for various sheet metals are stated clearly. Keywords: Thermal drilling, Applications, Thermal drill tools, Sheet metals